Design and development of an electronic device for data transmission with universal coverage (2014)
This paper presents the design and development of an electronic device with cellular and satellite coverage for localization and tracking of mobile assets in Colombia (public transport, freight, carriers, etc.). The development of this product integrates hardware, software and communication interfaces. It is aligned with a need identified in the market by the company One Solution Position: OSP LTDA. With this technology transfer we intend to improve the offer of wireless services for mobile asset tracking with a solution that covers the following features: dual operation (cellular/satellite), versatile, economical, low-power consumption, and based on international standards FCC and CE Mark.